Mumps encephalitis with akinesia and mutism. Issue 4 (25th March 2015) - Suga, Kenichi; Goji, Aya; Shono, Miki; Matsuura, Sato; Inoue, Miki; Toda, Eiko; Miyazaki, Tatsushi; Kawahito, Masami; Mori, Kazuhiro
Abstract Measles‐rubella‐mumps vaccination is routine in many countries, but the mumps vaccine remains voluntary and is not covered by insurance in Japan. A 5‐year‐old Japanese boy who had not received the mumps vaccine was affected by mumps parotitis. Several days later, he presented with various neurological abnormalities, including akinesia, mutism, dysphagia, and uncontrolled respiratory disorder. Mumps encephalitis was diagnosed. Despite steroid pulse and immunoglobulin treatment, the disease progressed. Magnetic resonance imaging showed necrotic changes in bilateral basal ganglia, midbrain, and hypothalamus. At 1 year follow up, he was bedridden and required enteral feeding through a gastric fistula and tracheostomy. Mumps vaccination should be made routine as soon as possible in Japan, because mumps encephalitis carries the risk of severe sequelae.